INTERNATIONAL SECURITY RELATIONS AND POST-IMPERIAL ORDERS - RADU-SEBASTIAN UNGUREANU (Challenges of the Knowledge Society)
This paper intends to investigate the relations between former imperial powers and new sovereign states succeeding an empire in the field of international security, particularly when involving the use of force. Despite their stated attachment to the normative principles of what we usually call “Westphalian order”, former imperial powers continue to interfere in the domestic affairs of these new states, especially those unable to exercise their sovereignty efficiently and legitimately. One could say that, by military interventions, these powers deny the sovereignty of weak states in the regions once under their control; but the preparation of these missions makes the actions not to be interpreted as expressions of an imperialist attitude. I consider there are two major ideal-types that could better explain such interventions. In a power-oriented postimperial order, the intervention of a former empire is the result of the projection of its national interests and identities. In a norm-oriented post-imperial order, the sense of moral responsibility of the former imperial power is the main reason for its interference. The intervention’s legitimacy and suitability require domestic and international support. This paper, grounded on a constructivist approach, intends to contribute to the understanding of international security issues in terms of a world shaped by actors’ interests and identities and the dynamics of their relations. The identified ideal-types of post-imperial orders consider both material and cultural factors. The analytical elements that may link extremely different situations are the socially variable interpretations of past and present.